The Role Of Inflation On Economic Stability In An Islamic Economic Perspective - Surya Saputra, Alfin Rahmawan (Institut Agama Islam Sumatera Barat, 2024)
This research aims to understand Indonesia's current inflation rate, its impact on purchasing power and economic stability, and the Islamic perspective on inflation and potential policy solutions. This research uses a qualitative approach with a type of literature study by reviewing books, literature, records, and reports related to the problem to be solved. The study found that Indonesia's inflation rate has fluctuated over the past four years, and has recently shown a downward trend due to falling prices in certain sectors. The predicted inflation rate at the end of 2024 is 2.4%. Inflation can directly affect purchasing power, with rising inflation eroding people's ability to purchase goods and services. This, in turn, impacts economic stability. Islamically, stabilizing the prices of basic necessities and equitable distribution of wealth are key to controlling inflation and maintaining economic stability. For Indonesia, the government should continue to implement policies to manage factors that affect inflation, such as demand, production costs, money supply, energy prices, and taxes.